Probing the diversity of chloromethane-degrading bacteria by comparative genomics and isotopic fractionation - Nadalig, Thierry; Greule, Markus; Bringel, Françoise; Keppler, Frank; Vuilleumier, Stéphane (Frontiers in Microbiology, 2014)
Chloromethane (CH3Cl) is produced on earth by a variety of abiotic and biological processes. It is the most important halogenated trace gas in the atmosphere, where it contributes to ozone destruction. Current estimates of the global CH3Cl budget are uncertain and suggest that microorganisms might play a more important role in degrading atmospheric CH3Cl than previously thought. Its degradation by bacteria has been demonstrated in marine, terrestrial, and phyllospheric environments. Improving our knowledge of these degradation processes and their magnitude is thus highly relevant for a better understanding of the global budget of CH3Cl. The cmu pathway, for chloromethane utilisation, is the only microbial pathway for CH3Cl degradation elucidated so far, and was characterized in detail in aerobic methylotrophic Alphaproteobacteria. Here, we reveal the potential of using a two-pronged approach involving a combination of comparative genomics and isotopic fractionation during CH3Cl degradation to newly address the question of the diversity of chloromethane-degrading bacteria in the environment. Analysis of available bacterial genome sequences reveals that several bacteria not yet known to degrade CH3Cl contain part or all of the complement of cmu genes required for CH3Cl degradation. These organisms, unlike bacteria shown to grow with CH3Cl using the cmu pathway, are obligate anaerobes. On the other hand, analysis of the complete genome of the chloromethane-degrading bacterium Leisingera methylohalidivorans MB2 showed that this bacterium does not contain cmu genes. Isotope fractionation experiments with L. methylohalidivorans MB2 suggest that the unknown pathway used by this bacterium for growth with CH3Cl can be differentiated from the cmu pathway. This result opens the prospect that contributions from bacteria with the cmu and Leisingera-type pathways to the atmospheric CH3Cl budget may be teased apart in the future.